Sulfur Amino Acids: From Prebiotic Chemistry to Biology and Vice Versa - Youssef-Saliba, Sparta; Vallée, Yannick (Synthesis, 2021)
Two sulfur-containing amino acids are included in the list of the 20 classical protein amino acids. A methionine residue is introduced at the start of the synthesis of all current proteins. Cysteine, thanks to its thiol function, plays an essential role in a very large number of catalytic sites. Here we present what is known about the prebiotic synthesis of these two amino acids and homocysteine, and we discuss their introduction into primitive peptides and more elaborate proteins.1 Introduction2 Sulfur Sources3 Prebiotic Synthesis of Cysteine4 Prebiotic Synthesis of Methionine5 Homocysteine and Its Thiolactone6 Methionine and Cystine in Proteins7 Prebiotic Scenarios Using Sulfur Amino Acids8 Introduction of Cys and Met in the Genetic Code9 Conclusion
Keywords: prebiotic chemistry; abiogenesis; cysteine; methionine; homocysteine; peptides; proteins